The impact of business innovations on brand value - Janošková, Katarina (Mednarodno inovativno poslovanje, 2018)
This article deals with interaction between business innovations and brand value. Innovation and brand equity are two important dimensions that drive businesses today; innovation in particular is a primary determinant of brand equity. Innovations and brand value are two key strategic assets that play important role in company growth and success. The aim of the research is demonstrating a statistically siginificant dependence between the brand value and innovations, which in our research are represented by R&D expenditures. Expenditure on research and development is taken in absolute terms, but also in relative terms as a percentage of revenue. Article contains basic theoretical background of this topic and results of research focused on confirming the dependence between these two parameters. The research is carried out on a sample of fourteen global brands (Google, Apple, Amazon, Microsoft, Samsung, Shell, IBM, Mercedes-Benz, Oracle, Siemens, Honda, Cisco, Intel, Nestlé) with application of mathematical-statistical apparatus. The analysis is carried out by comparison of selected brand values provided by consultative company Brand Finance with innovations represented by R&D expenditure (USD, percentage of sales).
Keywords: brand value; correlation; innovations; inovacije; korelacija; vrednost blagovne znamke